Refleksi Teologis Kitab Yeremia tentang Pesan Sang Nabi Bagi Orang-orang Buangan - Sitorus, Herowati (Sekolah Tinggi Agama Kristen Negeri Toraja, 2018)
The Book of Jeremiah is very difficult to understand because the events are not in chronological order. Jeremiah understanding by critical studies provides a more complete understanding even though it was written not in chronological order. This study is built on the understanding of the supervisor writing the book that would expose us, the author of the book, the time and place of writing, the outline of the contents of the book. Historical background, social and political book is also very necessary to study to provide a broader picture of the book of Jeremiah. Jeremiah did his job during the reforms of Josiah in 621 BC, (2) reign of Jehoiakim king in 609 BC, (3) the reign of King Jehoiachin in December 598 to March 597 BC, and (4) of Zedekiah in 597-587 BC.Abstrak: Kitab Yeremia merupakan kitab yang sangat sulit dipahami karena peristiwa-peristiwa yang terjadi di dalamnya tidak berlangsung secara teratur. Memahami Yeremia dengan kajian-kajian yang kritis memberikan sebuah pemahaman yang lebih lengkap sekalipun tidak ditulis secara urut. Kajian ini dibangun atas pemahaman tentang penulisan kitab yang akan menyingkapkan tentang penulis kitab, waktu dan tempat penulisan, garis besar kitab. Latar belakang sejarah, baik secara politik dan ekonomi juga sangat penting untuk dikaji untuk memberikan gambaran yang lebih luas tentang kitab Yeremia. Yeremia melakukan pekerjaannya selama reformasi Yosia pada tahun 621 SM; pemerintahan raja Yoyakhim pada tahun 609; pemerintahan raja Yehoakim pada Desember 598 hingga Maret 597 SM, serta pada masa raja Zedekia tahun 597-587 SM.